Screening for drought resistance during germination of modern and old Iberian wheat cultivars - Pavia, Ivo; Rocha, Luis; Moutinho-Pereira, Jose; Lima-Brito, Jose; Correia, Carlos (Acta Botanica Croatica, 2019)
Climate change is expected to reduce water availability in several wheat (Triticum aestivum L.) growing areas. Drought, during and immediately after sowing can compromise germination, seedling development, and ultimately crop yield. Our study’s objective was to investigate early drought stress resistance and evaluate genetic diversity of four bread wheat cultivars – three modern elite germplasm lines (‘Antequera’, ‘Jordão’ and ‘Roxo’) and an ancient Portuguese cultivar (‘Mestiço’) – at five water potentials, ranging from 0 to –1.5 MPa. Germination was annotated daily during eight days. Dry and fresh weights as well as root and shoot growth were measured. Genetic variability among cultivars was evaluated using start codon targeted (SCoT) markers. Overall, when water potential was lowered, germination rate and seedling growth were delayed. Final germination percentages were only affected by the higher stress intensity. This study reinforces the importance of research into ancient wheat cultivars, such as ‘Mestiço’. This cultivar showed the highest genetic difference when compared with the remaining cultivars. ‘Mestiço’ presented the highest coleoptile size, high vigor index values, and the lowest variation in water content due to stress conditions. Therefore, it may be able to germinate in extremly dry soil and be the least affected by drought stress. Still, due to the comparatively reduced yield of older wheat cultivars, stress tolerance should be researched within elite cultivars. Among these, Jordão revealed particularly good germination and early biomass development characteristics across water potentials, presenting a likely choice for future studies under drought stress conditions.